The contributions of Social Cartography approach to education policy analysis (Práxis Educativa, 2009)
This article describes the main features of social cartography to the study and analysis of educational policies. One of the main advantages of social cartography is that it allows the visualization – and eventually the integration – of different perspectives that conceptualize the phenomenon being investigated and verifies these perspectives as they integrate and relate to one another. Social cartography has the potential for the analysis of educational policies in search of the implications of the various discourse or discursive perspectives as well as their inter-relation. Therefore, social cartography becomes a valuable tool for analysis that can be combined with other methods and techniques for investigating numerous educational problems. Keywords: Social cartography. Research. Educational policies.